Estimation of radiological parameters associated with mining and processing of coastal sand in Binh Dinh province, Vietnam - Nguyen, Van Dung (Nuclear Science and Technology, 2018)
In Vietnam mining industry is significantly contributing to the socio-economic development. For the industrialization, many kinds of minerals are being exploited and processed that caused the Earth surface to be disconcerted leading to the increase of erosion of soil that possibly carries radioactive nuclides of the natural radioactive chains. Mining could cause increasing radioactive background to the miners as well as to the public members around the mines. This paper presents radiological parameters associated with mining and processing ilmenite minerals in coastal sand for titanium for export in Binh Dinh province, Central Part of Vietnam.